2014
DOI: 10.1371/journal.pone.0084732
|View full text |Cite
|
Sign up to set email alerts
|

An Entomopathogenic Strain of Beauveria bassiana against Frankliniella occidentalis with no Detrimental Effect on the Predatory Mite Neoseiulus barkeri: Evidence from Laboratory Bioassay and Scanning Electron Microscopic Observation

Abstract: Among 28 isolates of Beauveria bassiana tested for virulence against F. occidentalis in laboratory bioassays, we found strain SZ-26 as the most potent, causing 96% mortality in adults at 1×107 mL−1conidia after 4 days. The effect of the strain SZ-26 on survival, longevity and fecundity of the predatory mite Neoseiulus (Amblyseius) barkeri Hughes were studied under laboratory conditions. The bioassay results showed that the corrected mortalities were less than 4 and 8% at 10 days following inoculation of the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 26 publications
4
39
0
1
Order By: Relevance
“…Er et al (2008) reported that Metarhizium anisopliae (Metschnikoff) Sorokin. was generally found to be pathogenic to Coccinella septempunctata L. and the mortality of adult was 47.61%, while Wu et al (2014) reported that B. bassiana strain SZ-26 showed high toxicity ag ai n st F ra n k lin i el la o ccid en ta l i s ( P er ga n d e) (Thysanoptera: Thripidae) but not a detrimental effect to predatory mite Neoseiulus (Amblyseius) barkeri (Hughes) (Acarina: Phytoseiidae).…”
Section: Introductionmentioning
confidence: 99%
“…Er et al (2008) reported that Metarhizium anisopliae (Metschnikoff) Sorokin. was generally found to be pathogenic to Coccinella septempunctata L. and the mortality of adult was 47.61%, while Wu et al (2014) reported that B. bassiana strain SZ-26 showed high toxicity ag ai n st F ra n k lin i el la o ccid en ta l i s ( P er ga n d e) (Thysanoptera: Thripidae) but not a detrimental effect to predatory mite Neoseiulus (Amblyseius) barkeri (Hughes) (Acarina: Phytoseiidae).…”
Section: Introductionmentioning
confidence: 99%
“…Efficacy of B. bassiana was similar to spinetoram and NNI-1171 among the remaining treatments. Significant reduction in the numbers of F. occidentalis larvae, adult or soil-dwelling stages was seen in different laboratory or greenhouse studies using commercial or local isolates of B. bassiana [13,19,10,20,21]. However, data on the field efficacy of B. bassiana in lettuce, especially in California is lacking and the current studies provide useful insights into the understanding of field efficacy of a commonly available entomopathogenic fungus.…”
Section: Studymentioning
confidence: 82%
“…On the fungus' side, there are several accounts on the mode of action towards the pest, such as the above-mentioned secretion of a glutinous substance by Clonostachys rosea conidia which conglutinate nematodes (Zhang et al, 2008), proliferation in the insect haemocoel (Zhang et al, 2012), penetration of the insect's integument (Amnuaykanjanasin et al, 2013), adherence to the insect's cuticle (Güerri-Agulló et al, 2010), fungal colonisation of the whole insect (Wu et al, 2014), and invasion of the target pest by hyphae (Toledo et al, 2010). Further, parasitizing of the fungal PPP on eggs has been described (Braga et al, 2008;Carvalho et al, 2010;Pau et al, 2012), as well as reduced survival of pupae, reduced rate of juveniles hatching from eggs (Sahebani and Hadavi, 2008) or death of larvae that hatched from treated eggs (Mochi et al, 2010).…”
Section: Behaviour Of Microbial Ppps In the Plant Pestmentioning
confidence: 99%